Outpatient prescription drug interactions at a city-affiliated healthcare center in Vietnam - Minh Cuong Nguyen; Dao Phuong Nguyen; Quang Loc Duyen Vo; Rebecca Susan Dewey; Minh Trung Nguyen; Quoc Quan Ly; Tu Nguyet Tran (GarVal Editorial Ltda., 2024)
Context: Adverse drug interactions increase the risk of hospitalization, treatment costs, unfavorable treatment outcomes, and prolonged hospital stays. However, there are a limited number of studies conducted in city-affiliated healthcare settings in Vietnam. Aims: To identify drug interactions in outpatient treatment prescriptions at a city-based healthcare center in the southern region of Vietnam. Methods: A cross-sectional descriptive study was conducted on outpatient treatment prescriptions stored in the outpatient department of a city-affiliated healthcare center from January to June, 2023. The study used two databases for drug interaction checking: the Drug Interactions Checker and Medscape Interactions Checker. Univariate and multivariate regression analyses were used to identify predictors of clinically significant drug interactions. Results: Among 1203 surveyed prescriptions, 36.7% contained at least one clinically-significant drug interaction, with 3% of prescriptions having severe interactions. The highest frequency of drug interactions involved amlodipine and metformin (9.9%). Patients with five or more prescribed medications (OR = 3.305; 95% CI: 2.320-4.708), hypertension (OR = 7.142; 95% CI: 4.658-10.950), dyslipidemia (OR = 2.242; 95% CI: 1.665-3.020), and non-insulin-dependent diabetes (OR = 2.447; 95% CI: 1.817-3.295) had a higher likelihood of experiencing clinically significant drug interactions. Conclusions: This study revealed that over one-third of outpatient prescriptions were associated with clinically-significant drug interactions. This study highlights the importance of clinical pharmacists screening prescriptions to detect and reduce interactions, as well as the application of computerized alert systems with intelligent screening software to minimize drug interactions.